Social capital, innovation and economic growth - Thompson, Maria João Ribeiro (2015)
Multidisciplinary innovation is the engine of growth of an increasing number of economies. Innovation output depends increasingly on information sharing and cooperation between creative agents. Sharing and cooperation requires the existence of generalised trust. Social capital consists of trust and trust-based networks. Our main goal is to illustrate theoretically the importance of social capital to the growth of an innovation economy.